2007
DOI: 10.2193/2005-640
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Survival of Radiotagged and Banded Northern Bobwhites in Georgia

Abstract: Numerous studies of behavior and ecology of northern bobwhites (Colinus virginianus) have depended on radiotagging and telemetry for data collection. Excluding the presumably short‐term effects of trapping, handling, and attaching radiotransmitters, researchers often assume that little bias is associated with estimating survival and behavioral parameters associated with this technique. However, researchers have not adequately examined these effects on organisms being investigated and have thus assumed demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 30 publications
5
59
4
Order By: Relevance
“…The survival rates derived from this study are lower estimates from those in a high-quality habitat (Palmer and Wellendorf 2007;Terhune et al 2007), but higher than those reported in areas of limited habitat (Burger et al 1995a;Corteville 1998). The analysis showed weak relationships between bobwhite breeding season survival and the explanatory variables-confidence intervals included zero for the parameter estimates.…”
Section: Survivalcontrasting
confidence: 67%
“…The survival rates derived from this study are lower estimates from those in a high-quality habitat (Palmer and Wellendorf 2007;Terhune et al 2007), but higher than those reported in areas of limited habitat (Burger et al 1995a;Corteville 1998). The analysis showed weak relationships between bobwhite breeding season survival and the explanatory variables-confidence intervals included zero for the parameter estimates.…”
Section: Survivalcontrasting
confidence: 67%
“…Researchers should also design studies which examine the effect of banding and radio-tagging on individuals, and also evaluate which methods provide the most reliable demographic data (Terhune et al, 2007;Palmer and Wellendorf, 2007;Buner and Schaub, 2008). These devices should be fitted a couple of weeks before the birds are released to allow full acclimatisation to them.…”
Section: Markingmentioning
confidence: 99%
“…Bobwhite quail: radio-transmitters, autumn population abundance counts (quadrat and point) have been used (Wellendorf et al, 2004;Wellendorf and Palmer, 2005), as has mark-recapture via trapping (Terhune et al, 2006a, b;Terhune et al, 2007;Palmer and Wellendorf, 2007). Malleefowl (from Sims, 2000): 24 birds out of a total of 67 released were radio-tagged and tracked for a few days to six months post-release.…”
Section: Continued Habitat Managementmentioning
confidence: 99%
“…Northern Bobwhites are characteristically poor dispersers (Lehmann 1946, Murphy and Baskett 1952, Smith et al 1982) that exhibit strong seasonal selection for habitats (e.g., Williams et al 2000, Lohr et al 2011 and have low annual survival driven by diverse predator assemblages (Burger et al 1994, Rollins and Carroll 2001, Cox et al 2004, Terhune et al 2007). Life-history theory predicts that low survival in r-selected species should have less influence on population growth rates than breeding productivity (Saether andBakke 2000, Stahl andOli 2006), which has been supported with empirical research from Northern Bobwhite populations at southern latitudes (DeMaso et al 2011).…”
Section: Introductionmentioning
confidence: 99%